2018
DOI: 10.1111/pan.13379
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anesthesia for children with mucopolysaccharidoses: A retrospective analysis of 54 patients

Abstract: Patients with mucopolysaccharidoses are at high risk for anesthesia-related complications. Remote location anesthesia is associated with increased risk for complications, and older age is associated with increased risk for difficult intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Previous case series addressed the issue of airway techniques in MPS, but did not provide direct comparative assessments taking essential confounding factors into account …”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous case series addressed the issue of airway techniques in MPS, but did not provide direct comparative assessments taking essential confounding factors into account …”
Section: Discussionmentioning
confidence: 66%
“…In nonsyndromic children, the risk for perioperative critical events decreases with age . However, it has been proposed that due to disease progression during the natural history of MPS, the risk for intubation problems might paradoxically increase . Nevertheless, after adjustment for multiple confounders, we found that perioperative adverse events did not increase with age in our multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, patients with MPS type II have increased incidence of difficult airway compared to the general patient population and require repeated MRI to follow the progression of the disease . Moreover, upper airway obstruction becomes more troublesome as disease progresses and with increasing age . Therefore, patients with MPS II require sedative drugs that provide reliable levels of sedation without causing airway obstruction.…”
Section: Discussionmentioning
confidence: 99%